Chapter Unfolding patterns of revolt - Braidotti, Rosi (Amsterdam University Press, 2023)
This article deals with art, fashion design, and cultural practice as both critique and creativity. It analyses artworks by William Kentridge, Sue Austin, and Lina Iris Viktor, as well as the fashion of Viktor & Rolf, reading these different works as modes of resistance and revolt against current forms and relations of power and knowledge. The authors place emphasis on new materialism and posthuman theory as theoretical frameworks that expand the range of cultural critique. They add a thematic focus on the actual bodies, the materials of cultural action, and the role of non-human elements in the making of artworks. With reference to feminist, decolonial and indigenous theories, the article analyses the workings of counter-cultural memories in contemporary art and fashion design practices.